Agriculture Subsidy Expenditures in Karnataka - Sree R, Shilpa; S Katti, Medhavini (International Journal of Psychosocial Rehabilitation, 2020)
India’s most of the population depends on agriculture sector but agriculture investment should include improvements in land, equipment, development of natural resources & development of human and social capital & physical capital formation. Human capital is the stock of knowledge, expertise or management ability. It is directly influenced by educational training. The upshot of current economic thinking is that the agricultural subsidies expenditure is useful or not. The main objectives of subsidies is two, that keeps food grains low and avoids food inflation & the latter ensures farmers income security. This paper basically focuses on agriculture subsidies expenditure in Karnataka and to know the distribution of various subsidies. This study is based on secondary data collected from Budget estimation India, ministry of Agriculture and finance, directorate of economics & statistics, economy survey.